TEORI S.R. RANGANATHAN FIVE LAWS OF LIBRARY SCIENCE DALAM PENGEMBANGAN KOLEKSI PERPUSTAKAAN - Almer Samantha Hidaya (Fihris: Jurnal Ilmu Perpustakaan dan Informasi, 2020)
A Library is an institution in the field of information provider services oriented to the needs of users. Five library laws put forward by S.R. Ranganathan (books are for use, every reader his book, every book its reader, save the time of the reader and the staff, library is a growing organism) has become one of the references in library collections development that are oriented to user needs. Implementation of five library laws according to Ranganathan are (1) Library collections must be regularly evaluated. The results of this evaluation can then be used as a reference in weeding activities. It is intended that each book can be used optimally. (2) A series of procurement procurement proseas that include user analysis, selection, selection, and procurement policies must be oriented to user needs. It aims to make every information that users need available in the library. (3) Accuracy in the processing and display management becomes important in information retrieval. It is intended that every book in the library can be accessed. (4) Libraries must provide easy access to users to get information as effectively and efficiently as possible. This is so that users do not waste time looking for collections in the library. (5) Libraries must adapt to the changing environment that is always developing. The development and fulfillment of a stable source of information aims to keep all parts of the library current and reliable.Keywords: S.R. Ranganathan, five laws of library science, library collections development